Challenges faced by student teachers of felte, ulis, vnu in designing an esp course syllabus = Khó khăn giáo sinh gặp phải trong việc xây dựng khung chương trình tiếng anh chuyên ngành - Giang, Thanh Trà (2021)
Given the explosive growth of globalization, technology advancement, and international job opportunities, English for Specific Purposes (ESP) has gained a vital place in the language teaching world. Despite its popularity, little research has been conducted to perceive the status quo of ESP teachers and their difficulties in a new working environment, and even less for pre-service teachers. With such inadequate understanding of pre-service teachers’ situation in ESP practice, especially in Vietnam context, this study is carried out to shed light on the challenges that student teachers of University of Languages and International Studies (ULIS) encounter while designing an ESP syllabus as a project of their ESP Methodology course. From the perspectives of approximately one hundred student teachers and four ESP lecturers, the research also takes into account the root of the problems, and suggests possible solutions to overcome these challenges. Questionnaires, semi-interviews, and document analysis are employed to achieve the aim. The results revealed that student teachers were more likely to confront with intrinsic challenges such as dealing with pedagogical knowledge or keeping motivation for the project, and the main cause of these difficulties lay behind the lack of experience in ESP teaching. As suggested by both groups of participants, consultation with the instructor and self-study might assist student teachers to cope better in those situations. Apart from major findings, several recommendations for the projects, ESP Methodology course, and English Teacher Education program were also given.